PEMBELAJARAN MATEMATIKA DALAM MENGEMBANGKAN KEMAMPUAN KOGNITIF ANAK USIA 4-5 TAHUN - Ardiana, Reni; Ika Pratiwi, Yuni; Agustina Dwi H, Rinawati (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2024)
This study aims to explore how mathematics learning contributes to the cognitive skill development of children aged 4-5 years. The subjects of this study are children aged 4-5 years. Using a qualitative approach, this research observes the teaching strategies employed and children's responses to learning. Data collection techniques were conducted through observations and interviews. The results show that play-based approaches, exploration, and interactive technology have a positive impact on children's critical thinking and problem-solving abilities. Keywords:Mathematics Learning, Cognitive, Early Childhood